2022
DOI: 10.4236/ape.2022.122012
|View full text |Cite
|
Sign up to set email alerts
|

A 5-Minute Rest Period Weakens the Phenomenon of History Dependence of Freely Chosen Pedalling Cadence and Entails a Borderland Observation

Abstract: Background: It was recently reported that the freely chosen cadence at the end of a bout of pedalling depended on relatively high and low preset cadences applied at the beginning of the bout. This was denoted as a phenomenon of motor behavioural history dependence. Objective: The present study aimed at expanding that recent finding by testing whether the described history dependence occurred if 5-min rest was incorporated between the initial pedalling at preset cadence and the final pedalling at freely chosen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…In another study, also performed on recreationally active individuals, it was shown that 5-min rest applied between initial pedalling at a low preset target (50 rpm) cadence and subsequent pedalling at freely chosen cadence caused the history dependence phenomenon to be averted. This was interpreted as a weakening of the history dependence phenomenon (Sheikulislami et al, 2022). In these previous studies, participants were healthy and recreationally active individuals and, thus, not competitive cyclists who are accustomed to a considerable amount of cycling, as in the present study.…”
Section: Discussionmentioning
confidence: 54%
“…In another study, also performed on recreationally active individuals, it was shown that 5-min rest applied between initial pedalling at a low preset target (50 rpm) cadence and subsequent pedalling at freely chosen cadence caused the history dependence phenomenon to be averted. This was interpreted as a weakening of the history dependence phenomenon (Sheikulislami et al, 2022). In these previous studies, participants were healthy and recreationally active individuals and, thus, not competitive cyclists who are accustomed to a considerable amount of cycling, as in the present study.…”
Section: Discussionmentioning
confidence: 54%
“…Mean values from the left and the right pedal were calculated for each of these values, before further analysis. This procedure of analysis has previously been applied ( 18 , 19 ). For examples of a tangential and radial pedal force profiles, the reader is referred to previous publications ( 19 , 20 ).…”
Section: Methodsmentioning
confidence: 99%